Influence of Parental Perception on Students’ Willingness to Pursue Vocational Careers: A Synthesis of Literature - Kennedy, Margaret George; Chizoba, Emelie Celestina (Advances in Social Sciences Research Journal, 2025)
This position paper examines the influence of parental perception on students’ willingness to pursue vocational careers, drawing on a synthesis of current literature from African and Asian contexts. Findings consistently demonstrate that parents’ beliefs, expectations, cultural values, and understanding of vocational pathways significantly shape students’ career decisions. In many societies, vocational education is perceived as inferior to academic professions, contributing to stigma, low enrolment, and reduced student confidence in Technical and Vocational Education and Training (TVET). Misconceptions about income potential, global relevance of skilled trades, and employment opportunities further reinforce negative parental attitudes. Conversely, studies show that when parents are informed about the economic and developmental benefits of vocational careers, they become strong advocates for their children’s participation. The paper argues that school counsellors play a central role in reshaping parental perceptions and supporting evidence-based career guidance. A gap remains in the literature regarding structured parent-focused interventions and culturally responsive counselling models that can realign parental beliefs with contemporary labour market realities. The paper concludes with suggestions for policy, school counselling practice, and parental engagement strategies aimed at improving students’ willingness to pursue vocational careers.